1996
DOI: 10.1007/s002689900150
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Smooth Muscle Tumors: Diagnostic Dilemmas and Factors Affecting Outcome

Abstract: We reviewed the 46 gastric stromal tumors that were treated at our institution between 1958 and 1992. The most common presenting symptoms were gastrointestinal bleeding, pain, and fatigue or malaise. The tumors ranged from 4 to 150 mm, with surgery most often being a wedge excision or partial gastrectomy. Abdominal computed tomography was the most specific diagnostic test obtained preoperatively. Factors associated with decreased survival included size >/= 8 cm (p = 0.02), more than 0-3 mitoses per 10 HPF (p <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 12 publications
2
26
0
2
Order By: Relevance
“…Massive intraperitoneal bleeding, as occurred in our patient, is an exceptional complication associated with high mortality rates [12, 13]. No case of hemoperitoneum was reported in the retrospective studies by Cooper et al [9]and Sanders et al [10]. Tsianos et al [14]found 12 cases of intraperitoneal hemorrhage in a review of the literature of more than 1,100 cases of smooth muscle tumors of the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Massive intraperitoneal bleeding, as occurred in our patient, is an exceptional complication associated with high mortality rates [12, 13]. No case of hemoperitoneum was reported in the retrospective studies by Cooper et al [9]and Sanders et al [10]. Tsianos et al [14]found 12 cases of intraperitoneal hemorrhage in a review of the literature of more than 1,100 cases of smooth muscle tumors of the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…However studies of these tumors are limited and even large series have relatively few patients. Cooper et al [9]reviewed 102 cases reported during 30 years in two centers and Sanders et al [10]found 46 cases treated at the Lahey Clinic for 35 years. Gastric stromal tumors are more frequent in males than females and occur in adult patients, especially between the 5th and 7th decade.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, biopsies from endoscopy yield the diagnosis in less than 60% of the time. 10,11 Although some authors feel that more extensive resections may be necessary for high-grade leiomyosarcoma, 12 others believe that a wedge resection is sufficient for leiomyosarcomas. 8,9 Four major laparoscopic methods have been described for the resection of gastric leiomyoma.…”
Section: Discussionmentioning
confidence: 99%
“…The primary treatment of GIST is a surgical resection with a negative tumour free margin of at least 2 cm is recommended 18,19 . A meticulous surgical technique is necessary to avoid intra-operative tumour rupture, which is associated with a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%